The Local Government of Kulon Progo Regency Innovation in Subduing Capitalism through Community Empowerment - Muhammad Eko Atmojo; Helen Dian Fridayani (Universitas Muhammadiyah Tangerang, 2020)
Kulon Progo Regency is one of the districts that has many innovations, one of which is community empowerment in collaboration with a modern shop abbreviated as the shop name owned by the people (tomira). This research was motivated by the achievements of the Kulon Progo district government in carrying out development and innovation in the development of the Kulon Progo region by fully involving the Kulon Progo district community through community empowerment. This initiative was taken by the government of Kulon Progo Regency to improve community empowerment and protect the people of Kulon Progo Regency from various economic threats. Considering that in the past few years many modern shops have mushroomed in each district/city, so this is what makes Kulon Progo Regency move quickly to empower the community by collaborating between MSMEs or cooperative with modern shops. This study uses a qualitative method which case study approach. With the empowerment that has been done, the original products of Kulon Progo Regency or local products can be traded in modern stores so that local products in Kulon Progo Regency can compete with national products in these modern stores. The existence of such cooperation will indirectly improve the image of Kulon Progo Regency and lift the original products of Kulon Progo Regency. The lifting of the original products of Kulon Progo Regency will have a positive impact on the community, where indirectly the economy of the community will increase so that there will be prosperity for the community. Kabupaten Kulon Progo adalah salah satu kabupaten yang memiliki banyak inovasi, salah satunya adalah pemberdayaan masyarakat bekerja sama dengan toko modern disingkat nama toko yang dimiliki oleh masyarakat (tomira). Penelitian ini dilatarbelakangi oleh pencapaian pemerintah kabupaten Kulon Progo dalam melakukan pengembangan dan inovasi dalam pengembangan wilayah Kulon Progo dengan melibatkan sepenuhnya masyarakat kabupaten Kulon Progo melalui pemberdayaan masyarakat. Inisiatif ini diambil oleh pemerintah Kabupaten Kulon Progo untuk meningkatkan pemberdayaan masyarakat dan melindungi masyarakat Kabupaten Kulon Progo dari berbagai ancaman ekonomi. Menimbang bahwa dalam beberapa tahun terakhir banyak toko-toko modern telah menjamur di setiap kabupaten/kota, jadi inilah yang membuat Kabupaten Kulon Progo bergerak cepat untuk memberdayakan masyarakat dengan berkolaborasi antara UMKM atau bekerjasama dengan toko-toko modern. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus, dengan metode yang digunakan adalah dokumentasi. Dengan pemberdayaan yang telah dilakukan, produk asli Kabupaten Kulon Progo atau produk lokal dapat diperdagangkan di toko modern sehingga produk lokal di Kabupaten Kulon Progo dapat bersaing dengan produk nasional di toko modern ini. Adanya kerjasama tersebut secara tidak langsung akan meningkatkan citra Kabupaten Kulon Progo dan mengangkat produk asli Kabupaten Kulon Progo. Pencabutan produk asli Kabupaten Kulon Progo akan berdampak positif bagi masyarakat, di mana secara tidak langsung perekonomian masyarakat akan meningkat sehingga akan ada kesejahteraan bagi masyarakat.